Feeding habits of Holothuria (Stauropora) fuscocinerea (Echinodermata: Holothuroidea) in a Mexican Pacific reef - Maya-Alvarado, Brenda; Calva-Benítez, Laura-Georgina; Granja-Fernández, Rebeca; Pérez-López, Jessica; López-Pérez, Andrés (Revista de Biología Tropical, 2021)
Introduction: The importance of holothuroids in marine ecosystems is related to their feeding activities, which have been little studied in the eastern Pacific. Objective: To describe the feeding habits of the sea cucumber Holothuria (Stauropora) fuscocinerea and their bioturbation potential in La Entrega reef, México. Methods: The population size of H. (Stauropora) fuscocinerea was determined by means of four 20 x 4 m (320 m2) band transects, while the available sediment for the sea cucumbers and their feces were characterized in three stations (A-C) via granulometry and quantification of organic carbon and organic matter. Excretion rate was determined every 4 hr over a 24 hr period and the relationship between sea cucumber length and biomass and the excretion rate evaluated. Results: According to non-parametric permutation, ordination and percentage similarity analyses, sea cucumber feces mostly comprised a large proportion of small grains compared to the available sediment, indicating that H. (Stauropora) fuscocinerea is selective on grain size. Preliminary bioturbation potential of the species may reach up to 8.71 ± 0.17 kg day of sediment in the study area. Conclusion: The spatial distribution of H. (Stauropora) fuscocinerea in the study area is a product of its selective feeding activity, evidencing the preliminary importance of the species in the trophic dynamics of La Entrega reef.